2010
DOI: 10.1111/j.1530-0277.2010.01156.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐Wide Association Study of Alcohol Dependence Implicates a Region on Chromosome 11

Abstract: Background: Alcohol dependence is a complex disease, and although linkage and candidate gene studies have identified several genes associated with the risk for alcoholism, these explain only a portion of the risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
294
1
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 279 publications
(304 citation statements)
references
References 70 publications
5
294
1
1
Order By: Relevance
“…Accordingly, any single gene contributes only to a limited extent to the phenotypes observed in alcohol consumption (6). In contrast to alcohol addiction, which has been investigated in numerous genetic studies (5), including recent genome-wide association studies (GWAS) analyses (7)(8)(9), few genes regulating alcohol consumption in humans have been described-with the notable exception of alcohol dehydrogenase (3,5,10). This may, to some extent, reflect the complexity of the phenotype, because the genetic and environmental determinants of alcohol drinking behavior may vary over the lifespan, and there may be substantial heterogeneity of intake and measurement across different populations and studies.…”
mentioning
confidence: 99%
“…Accordingly, any single gene contributes only to a limited extent to the phenotypes observed in alcohol consumption (6). In contrast to alcohol addiction, which has been investigated in numerous genetic studies (5), including recent genome-wide association studies (GWAS) analyses (7)(8)(9), few genes regulating alcohol consumption in humans have been described-with the notable exception of alcohol dehydrogenase (3,5,10). This may, to some extent, reflect the complexity of the phenotype, because the genetic and environmental determinants of alcohol drinking behavior may vary over the lifespan, and there may be substantial heterogeneity of intake and measurement across different populations and studies.…”
mentioning
confidence: 99%
“…A second strategy is to narrow the phenotype and to analyze a more homogeneous sample. A GWAS analysis was performed on the COGA subset of European-American subjects (996 subjects overlap with this report) (32). This approach focuses the analysis on subjects recruited under a single ascertainment protocol for alcohol dependence, and the severity of illness in these subjects is high.…”
Section: Discussionmentioning
confidence: 99%
“…7,10,11 The relevant role of genetic factors both on alcohol consumption and dependence has been clearly demonstrated by genome-wide association study (GWAS) studies. [12][13][14][15][16] Moreover, studies on the genetic variations in bitter taste receptors have also shown that variations in TAS2R16 and TAS2R38 genes can influence alcohol intake [17][18][19] but not dependence. 19 On the contrary, very little is known about the possible contribution of genetic factors to alcohol preferences in humans.…”
Section: Introductionmentioning
confidence: 99%